2013
DOI: 10.4103/0259-1162.118957
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparison of ketofol (ketamine and propofol admixture) versus propofol as an induction agent on quality of laryngeal mask airway insertion and hemodynamic stability in children

Abstract: Background:In spite of being the preferred induction agent for LMA insertion, propofol has many undesirable side effects including dose-related cardiorespiratory depression and local pain at injection site. Ketofol as a novel induction agent has been introduced recently with comparable efficacy and improved hemodynamic controlObjective:To investigate ketofol as a suitable induction agent alternative to propofol for insertion of LMA in children considering insertion conditions, hemodynamic stability, local pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(35 reference statements)
4
17
0
1
Order By: Relevance
“…Another observation was stable haemodynamics and shorter apnea time in KP group as compared to P group. 17 The results of our study are also comparable to another done for insertion of laryngeal tubes under propofol or ketofol anesthesia. They showed significant results with p<0.05 with better insertion of laryngeal tube with minimal adverse airway responses and complications under ketofol (Group K ) induction as compared to propofol (Group P).…”
Section: Discussionsupporting
confidence: 82%
“…Another observation was stable haemodynamics and shorter apnea time in KP group as compared to P group. 17 The results of our study are also comparable to another done for insertion of laryngeal tubes under propofol or ketofol anesthesia. They showed significant results with p<0.05 with better insertion of laryngeal tube with minimal adverse airway responses and complications under ketofol (Group K ) induction as compared to propofol (Group P).…”
Section: Discussionsupporting
confidence: 82%
“…BIS values for awake patients emanated from 20 cohorts within 18 studies [ 14 , 16 , 19 34 ] (Additional file 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was similarly reported by Yousef and Elsayed in their study on children. 16 We found that co-induction with midazolam produced a significantly longer duration of apnoea compared to ketamine. This suppression of breathing effort is attributed to the synergistic action between midazolam and propofol at the common GABA receptor sites.…”
Section: Discussionmentioning
confidence: 72%